Identification of Factors Influencing the Commission of Burglaries - Donmez, Mustafa (2011)
As in many countries, burglary is a very serious crime in Turkey. Scientific methods and techniques are needed to solve complex burglary cases. This study is completed in the Bursa Police context since they classified many crime data conducive to scientific studies under a project called BEMTAP. The main purpose of this study is to examine the factors influencing the commission of burglaries, using an epid-criminological perspective. It can be argued that factors leading to the commission of a crime are important for formulating preventive strategies in the community. In this study, the contributing factors are categorized into three main groups of predictors, by adapting a disease triangle in epidemiology: opportunity factors (agent), offender factors (host), and environmental factors. Criminal method (technique) and time of burglary are conceived as the opportunity factors. Four personal or host characteristics of offender factors are age, gender, marital status, and education level. Distance between the home addresses of burglars and target houses and distance between target houses and police stations are examined as environmental factors. This epid-criminology perspective is thought as a basic framework for integrating two theories: routine activity theory and rational choice theory. Two hypotheses, using agent, host, and environmental factors as predictors, were proposed to test their relationships with the frequency of burglaries committed and with the likelihood of committing repeated burglaries. In measuring the relative influence of the predictor variables on the number of burglaries and on repeated burglaries, two different models were constructed and validated. For the first model of predictors of crime against property (burglary), Hierarchical Multiple Regression Analysis was performed. For the second model, a logistic model of the predictors of repeated burglaries was used and analyzed. The results show that offender factors are more influential than opportunity and environmental factors in explaining the variability in frequency of burglaries committed and the likelihood to commit repeated burglaries. In conclusion, the best way to reduce burglary rate is to focus on offender factors. Dealing with opportunity factors and environmental factors would also contribute to a decreased burglary rate